Sortilege and its Practitioners in Late Antiquity: My Lots are in Thy Hands. - AnneMarie Luijendijk; William E. Klingshirn (Editors) (Religions in the Graeco-Roman World, 2019)
Sortilege-the making of decisions by casting lots-was widely practiced in the Mediterranean world during the period known as late antiquity, between the third and eighth centuries CE. In My Lots are in Thy Hands: Sortilege and its Practitioners in Late Antiquity , AnneMarie Luijendijk and William Klingshirn have collected fourteen essays that examine late antique lot divination, especially but not exclusively through texts preserved in Greek, Latin, Coptic, and Syriac. Employing the overlapping perspectives of religious studies, classics, anthropology, economics, and history, contributors study a variety of topics, including the hermeneutics and operations of divinatory texts, the importance of diviners and their instruments, and the place of faith and doubt in the search for hidden order in a seemingly random world.